Pengaruh Motivasi Kerja, Lingkungan Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada Perusahaan WFO Masa Pandemi - hustia, Anggreany (Jurnal Ilmu Manajemen, 2020)
This research was conducted to determine the effect of work motivation, work environment, and work discipline on employee performance in operational company as a Work From Office in the Pandemic Era of Covid 19. This research was done because the researcher think that it was necessary to know how is the infuence among variables in Pandemic condition. Therefore, the company could prepare good human resources to face new normal Era. The object of the research was PT.CS2 Pola Sehat Palembang. The researcher gave the questionnaires to 74 employees as  the sample of the research. This research used multiple regression analyses, stimultaneous testing and individual testing.This results of the research conducted jointly between all the variables that illustrate that there was the influece of work motivation, work discipline, and work environment on employee performance. And the results of research individually known that there was the influence of work motivation and work environment and work discipline toward to  employee performance.